Evaluating User Acceptance of Virtual Class on Bali Melajah Portal Using Technology Acceptance Model and Importance Performance Analysis - Purnawan, I Putu Abdi; Sudarma, Made; Indra ER, Ngurah (Scientific Journal of Informatics, 2025)
Purpose: The purpose of this study was to evaluate the acceptance and performance of users of the Virtual Class application in the Bali Melajah Portal using the Technology Acceptance Model (TAM) and Importance-Performance Analysis (IPA). This study found the main components of adoption, evaluated performance disparities, and suggested ways to improve LMS adoption in secondary schools. Methods: This study used a quantitative approach through an online survey conducted to collect data from teachers and students. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to evaluate the relationship between the variables in the research model. IPA was used to evaluate system performance and determine areas for improvement. Results: The study showed that perceived ease of use significantly influenced perceived usefulness, which in turn affected attitudes and behavioral intentions. Meanwhile, behavioral intentions positively affected actual system use. Performance mismatch was found, with the lowest percentage of conformity of 97.76% for actual system use. Quadrant analysis highlighted that, although the system was perceived as useful and easy to use, involvement, accessibility, and institutional support were necessary for effective system use. Novelty: This study offers a two-pronged assessment of LMS adoption in secondary schools by combining TAM and IPA. Unlike earlier studies that only evaluated user perceptions or system performance separately, this paper provides a complete approach to maximizing government-supported digital learning platforms. These findings give policymakers and application developers knowledge to improve the adoption of Virtual Classroom LMS.